Involvement in physical fights among school attending adolescents: a nationally representative sample from Kuwait - Shaikh, Masood; Abio, Anne P.; Adedimeji, Adebola A.; Wilson, Michael (Behavioral Sciences, 2020)
Background: Interpersonal violence in school settings is an important public health problem worldwide. This study investigated the individual and social correlates for being involved in a physical fight amongst a nationally representative sample of school-attending adolescents in Kuwait. Methods: We carried out bivariate and multivariate analyses to determine the strength and direction of associations with adolescent involvement in problematic fighting behavior within a 12-month recall period. Results: Within a total sample of 3637, n = 877 (25.2%) of school-attending adolescents reported being involved in two or more physical fights during the recall period. The multivariate analysis indicated that being male (OR = 2.71; CI = 1.88-3.90), a victim of bullying (OR = 2.77; CI = 2.14-3.58), truancy (OR = 2.52; CI = 1.91-3.32), planning a suicide (OR = 2.04; CI = 1.49-2.78) and food deprivation (OR = 1.91; CI = 1.37-2.65) were associated with an increased risk of involvement in physical fighting. Peer support in the form of having close friends (OR = 0.85; CI = 0.76-0.96) was found to be associated with a reduced involvement in fighting behavior. Conclusion: The results, when taken together, suggest that supportive school environments may represent important settings for violence mitigation and prevention strategies.
Gesehen am 16.04.2020